Age and Psychological Characteristics of the Development of Students in Grades 6 and 7 in Schools - Fattohevna, Azimova Nazira (European Journal of Life Safety and Stability (2660-9630), 2022)
An important factor in the successful fulfillment of the goals and objectives of teaching a foreign language is to take into account the psychological and pedagogical features of teaching a foreign language at different levels. Knowing the personality traits of a particular age makes it possible to correctly determine the content and form of responsibility. The article discusses the problem of accounting for age and psychological characteristics of the development of students in grades 6-7 in schools.